I am having trouble with the following question:

Integrate the Taylor series

$$e^{(-t^2)} = \sum^\infty_{n=0} \frac{(-t^2)^n}{n!}$$ term-by-term to obtain the Taylor series for erf (error function) about a = 0.

Now I have integrated the first few terms and can see that the series converges, but I do not see how to turn it into another taylor series. $$\int\sum^\infty_{n=0} \frac{(-t^2)^n}{n!} dt =C+t - \frac{t^3}{3}+\frac{t^5}{10}-\frac{t^7}{42} +...$$

Can any one give me a hand with this?


$$\int \sum_{n=0}^\infty \frac{(-t^2)^n}{n!} dt$$ $$= \sum_{n=0}^\infty \int \frac{(-t^2)^n}{n!} dt$$ $$= \sum_{n=0}^\infty \int \frac{(-1)^n}{n!} t^{2n}dt$$ $$= \sum_{n=0}^\infty \left(\frac{(-1)^n}{n!} \int t^{2n}dt\right)$$ $$= \sum_{n=0}^\infty \left(\frac{(-1)^n}{n!} \frac{t^{2n+1}}{2n+1}\right)$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.